INTEGRATING PEER LEARNING AND INQUIRY CYCLE WITH PHET TO IMPROVE UNDERSTANDING OF DYNAMIC ELECTRICITY - Solihat, Dede; Darmawan, Deni; Omonovich, Khammataliev Dostnazar; Eshbekovich, Usarov Jabbor; Rakhimovich, Ergachev Rustam (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2025)
Most eighth-grade junior high school students often experience difficulties in understanding abstract and complex physics topics, such as dynamic electricity, which frequently leads to misconceptions and negatively impacts learning outcomes. To address this problem, researchers developed and tested an integrated learning strategy that combines peer teaching, the inquiry learning cycle model, and the use of PhET simulations, enabling students to conduct virtual experiments. This study used the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of 32 ninth-grade students of SMPN 1 Bayongbong, with a one-group pretest-posttest design to measure the learning impact. The validation of the learning tool was carried out by four experts, who obtained an average score of 0.89, indicating high theoretical feasibility. In terms of practicality, teachers gave an average rating of 91%, and students gave an average rating of 87%, both indicating a very good level of practicality. During four meetings, students took pretests and posttests, engaged in peer teaching activities, and learned concepts directly through PhET simulations. Concept understanding was measured through a structured test and then analyzed using the N-Gain method. In this study, the N-Gain score obtained was 0.57, indicating a moderate category. In addition to quantitative data, student observations and reflections showed positive impressions. These findings strengthen the evidence that this learning strategy can help students better understand the concept of dynamic electricity.